Pengembangan Media Pembelajaran Komik Situs-Situs Peninggalan Sejarah Pada Mata Kuliah Kepariwisataan Sejarah FKIP Unpatti - Natalya Claire Pessy; Jenny Koce Matitaputty; Bety D.S. Hetharion (Jurnal Ilmiah Wahana Pendidikan, 2022)
This research is actually intended to develop a learning media for comics on historical heritage sites in the Historical Tourism course in the History Education Study Program. This course studies the theory and practice of historical heritage sites in Maluku, how students should be able to become historical tour guides through this course. With the ADDIE learning design model starting from the stages of Analysis, Design, Development, Implementation and Evaluation. This study uses research and development methods that are used to produce certain products and test the effectiveness of these products. The location in this research is the History Education Study Program, FKIP UNPATTI, with data collection techniques, using instruments in the form of knowledge test sheets, and interviews. The results of this study indicate an increase in student learning outcomes as well as awareness in preserving God-given nature for the sustainability of the Maluku generation where there is a significant difference in the cognitive scores of learning media at historical heritage sites on the island of Ambon before and after the application of media from the acquisition of the t-count value. of -29.859 with a sig-tailed of 0.00, because 0.00 < from 0.05.